THE INFLUENCE OF TEACHERS AGE TOARDS THE TEACHING AND LEARNING PROCESS DURING PANDEMIC COVID 19 - Maulida, Maulida; Hamama, Syarifah Farissi; Aryani, Irma; Hasanah, Hasanah; Suryani, Suryani (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
ABSTRACT The purpose of the study was to see the extent of the problems that occurred in the field, especially in the aspect of teachers in carrying out the learning process during the pandemic. By knowing all the problems that teachers experience, they are expected to be able to provide solutions to various parties involved in the world of education to contribute to solving these problems together. This research activity was carried out from June 2020 to March 2021. The objects in this study were teachers who teach in SMA and SMP in the Greater Aceh region. The results showed that various kinds of problems occurred during the learning process, one of which was the age of the teacher. It can be seen that the age of the teacher has an effect on the learning process during the COVID-19 pandemic.